Studies on the antimicrobial properties of the volatile oil and the non-polar components from the leaves of Psidium guajava Linne (F. Myrtaceae) - Agbayani, Ma. Lynn Rachelle J.
This research is concerned primarily with the anti-microbial properties of the volatile oil and the non-polar components of the leaves of guava, Psidium guajava Linne (Fam. Myrtaceae).